Preparation process and formula of low-power sunlamp
Patent Information
- Application Number
- CN202611073046.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-09
AI Technical Summary
汞具有高毒性,不符合环保趋势;而单一氙气的光效和显色性仍有提升空间
1.显著提升光源寿命与稳定性:通过在真空钼丝炉中进行6-8小时、1050℃的高温除羟基处理,有效去除了石英玻璃中的OH基团,从根本上抑制了水分子对电极的氧化腐蚀,大幅降低了光衰,延长了光源寿命。
Smart Images

Figure CN122889648A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lighting manufacturing technology, and specifically relates to a preparation process and formula for a low-power lighting lamp. Background Technology
[0002] In the manufacturing process of low-power fluorescent lamps, the quality of the manufacturing process directly determines the luminous efficacy, lifespan, and consistency of the final product. Existing manufacturing processes generally suffer from the following drawbacks: First, in the preparation of the discharge inner liner, traditional sealing processes often fail to completely remove hydroxyl groups (OH groups) from the quartz glass. Under the action of a high-temperature electric arc, hydroxyl groups decompose to produce water vapor. This water vapor further reacts with the electrode material, leading to severe oxidation and sputtering of the electrodes. This not only reduces luminous efficiency but also forms a black adhesion layer on the inner wall of the quartz bulb, causing premature failure of the light source.
[0003] Secondly, in the filling, venting, and sealing processes, conventional flame sealing can easily lead to residual stress concentration inside the bubble shell, and oxygen from the air can easily mix in at the sealing moment, causing the internal filler to oxidize and deteriorate. At the same time, the lack of effective anti-oxidation protection measures during the outer tube sealing process causes the metal support and molybdenum rod to oxidize at high temperatures, increasing contact resistance and affecting the stability of light output.
[0004] Furthermore, regarding the filling gas formulation, traditional Xenon lamps often use a single xenon gas or a simple mixture of xenon and mercury. Mercury is highly toxic and does not align with environmental trends; while the luminous efficacy and color rendering index of single xenon gas still have room for improvement. Current technology lacks specific metal halide ratios optimized for the 12-75W low-power range and precise xenon-argon mixing ratios, preventing the light source from achieving optimal 3000-6000K color temperature and high color rendering index within this power range.
[0005] Furthermore, in the lamp holder assembly process, traditional wiring methods rely on manual winding and soldering, which is inefficient and inconsistent, and prone to problems such as incomplete soldering or short circuits. Therefore, developing a new process that integrates high-temperature hydroxyl removal, plasma sealing, inert gas protective sealing, and a specialized chemical formula is key to solving the aforementioned manufacturing challenges and improving the quality of low-power fluorescent lamps. Summary of the Invention
[0006] In view of this, the present invention provides a manufacturing process and formula for a low-power fluorescent lamp to solve or alleviate one of the technical problems existing in the prior art, and at least provides a beneficial alternative.
[0007] The technical solution of this invention is implemented as follows: a manufacturing process for a low-power fluorescent lamp, comprising the following steps: (1) Preparation of the discharge inner tube: Select a high-purity SiO2 quartz glass tube and heat it with a bubble machine to form an olive-shaped bubble; insert an electrode assembly with a spiral electrode head, and quickly press and seal the tube pins to the fusion point by heating them with a high-temperature flame in a sealing vehicle; place the sealed quartz bubble into a vacuum molybdenum wire furnace and operate at 1050℃ for 6-8 hours with a high vacuum environment to remove OH groups; after cooling to room temperature, add a customized filler from the other end; insert another electrode assembly with a spiral electrode head, adjust the electrode spacing and fix it; after filling with xenon and argon, use Plasma-Flame technology to seal the glass tube opening tightly, and then seal it again at the molybdenum sheet; cut off the excess glass tube and burn the opening; (2) Pretreatment of the stent: Prepare an irregularly shaped molybdenum stent, fit a ceramic insulating tube on the stent, and weld a degassing plate; (3) Assembly of inner liner and bracket: Weld one end of the bracket to the molybdenum rod of the discharge inner liner; after putting an insulating sleeve on the other end of the bracket, connect the molybdenum connecting rod and connect it by welding with molybdenum sheet; bend the end of the discharge inner liner near the lamp head, put on an insulating sleeve and connect another molybdenum connecting rod; put the assembly into the lamp body; (4) Sealing and venting of the outer tube: Fix the assembly, put on the outer UV-filtering quartz glass shell, and introduce inert gas for protection through the outer venting pipe; use a sealing machine to press to form a sealing interface; perform vacuum treatment to remove impurities, fill with protective gas, and then seal and cut the venting pipe; (5) Lamp holder assembly: Pass the molybdenum connecting rod through the metal lamp base tube at the bottom of the lamp holder and expose 3mm, then weld it; (6) Curing: Fill the lamp holder cavity with lamp holder fixing powder and dry and cure at 100-120℃.
[0008] Furthermore, the vacuum level of the high vacuum environment described in step (1) is 1×10^-4 Pa to 1×10^-5 Pa; The cooling rate of the slow cooling process is controlled at 30-50℃ / h; the power density of the Plasma-Flame is set to 2-4kW, and the scanning speed is 5-10mm / s to ensure that there are no bubbles or cracks in the sealing area.
[0009] Furthermore, the insulating sleeve described in step (3) is located between the bottom of the support bracket and the molybdenum sheet, and the length of the insulating sleeve covers more than 80% of the exposed part of the molybdenum connecting rod. The bending angle is 85-95 degrees, and the bending radius is greater than 5mm to prevent the quartz tube from breaking.
[0010] Furthermore, the inert gas mentioned in step (4) is high-purity nitrogen or argon, with an introduction flow rate of 0.2-1.0 L / min, and positive pressure protection is maintained throughout the sealing process; the vacuum degree of the vacuum treatment reaches the level of 10^-3 Pa, and the heating and degassing temperature is 350-450℃.
[0011] Furthermore, the welding described in step (5) is performed using resistance welding or micro-beam plasma welding, with a welding current of 50-150A and a welding time of 0.1-0.5 seconds, to ensure that a metallurgical bond is formed between the molybdenum connecting rod and the metal lamp base column, with a contact resistance of less than 5mΩ.
[0012] Furthermore, the custom filler comprises a metal halide consisting of sodium iodide, thulium iodide, and strontium iodide in a mass percentage ratio of 1:1-2:1-3.5. This ratio is used to form a halide cycle under the action of an electric arc, adjusting the color temperature to the range of 3000-6000K.
[0013] Furthermore, the mass percentage of xenon gas to argon gas introduced in step (1) is 100:0.5-1; this gas ratio is used to reduce the starting voltage to about 10000V and enhance the stability and penetration of the electric arc.
[0014] Furthermore, in step (6), the lamp holder fixing powder is a silicate composite powder; The drying and curing time is 20-40 minutes. The adhesive layer formed after curing has both insulation and shock absorption properties.
[0015] Furthermore, the sealing position of the discharge inner liner is sealed using a high-temperature oxy-fuel flame with a flame temperature of approximately 2000-2200℃ and a pressing pressure of 0.5-1.5 MPa, ensuring an airtight seal between the molybdenum sheet and the quartz glass tube without stress concentration.
[0016] Furthermore, the process is suitable for manufacturing low-power fluorescent lamps with a power of 12-75W; The prepared Xuguang lamp has a lamp efficacy greater than or equal to 100 lm / W, a color rendering index Ra greater than or equal to 90, and a starting voltage of 9800-10500V.
[0017] The embodiments of the present invention have the following advantages due to the adoption of the above technical solutions: 1. Significantly improves the lifespan and stability of the light source: By performing a high-temperature dehydroxylation treatment at 1050℃ for 6-8 hours in a vacuum molybdenum wire furnace, the OH groups in the quartz glass are effectively removed, which fundamentally inhibits the oxidative corrosion of the electrodes by water molecules, greatly reduces light decay, and extends the lifespan of the light source.
[0018] 2. Improve sealing quality and airtightness: Plasma-Flame technology is used for sealing. Compared with traditional flames, plasma has a higher temperature and more concentrated energy, resulting in faster sealing speed and a smaller heat-affected zone. This effectively reduces thermal stress and residual deformation inside the bubble shell, improving airtightness and explosion-proof performance.
[0019] 3. Optimized photoelectric performance: A specific ratio of sodium iodide, thulium iodide, and strontium iodide (1:1-2:1-3.5) enables optimal halogen cycling at high arc temperatures, improving luminous efficiency, precisely controlling the color temperature between 3000-6000K, and ensuring a high color rendering index of over 90. A xenon-argon ratio (100:0.5-1) optimizes startup characteristics and arc stability.
[0020] 4. Prevention of oxidation and contamination: During the sealing process of the outer tube, inert gas is continuously introduced for protection, which effectively prevents the oxidation of the molybdenum support and molybdenum rod during the high-temperature sealing process, ensuring good conductivity and reflectivity.
[0021] 5. Enhanced structural reliability: The plug-in welding process of the lamp holder (exposing 3mm of welding) combined with the curing treatment of silicone / fixing powder forms a fixed structure that combines rigidity and flexibility, ensuring the firmness of electrical connections and providing excellent shock resistance.
[0022] The above overview is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments, and features described above, further aspects, embodiments, and features of the invention will become readily apparent from the accompanying drawings and the following detailed description. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0024] Figure 1 This is a schematic diagram of the overall structure of the low-power sunrise lamp in an embodiment of the present invention; Figure 2 This is a flowchart illustrating the overall manufacturing process of the low-power sunrise lamp of this invention.
[0025] The markings in the diagram are as follows: 01, lamp holder; 01-1, mounting base; 01-2, metal lamp base column; 01-3, cavity; 01-4, connecting channel; 01-5, arc-shaped protrusion; 02, lamp body; 03, discharge inner liner; 04, sealing interface; 05-1, upper electrode molybdenum connecting rod; 05-2, lower electrode molybdenum connecting rod; 06, upper electrode assembly with spiral electrode head; 07, lower electrode assembly with spiral electrode head; 08, sealing molybdenum sheet; 09, molybdenum rod; 10, molybdenum sheet; 11, support bracket; 12, fixing part; 13, degassing plate; 14, inert gas; 15, insulating sleeve; 16, ceramic tube; 17, glass tube; 18, sealing position; 19, UV-filtering quartz glass shell. Detailed Implementation
[0026] In the following description, only certain exemplary embodiments are briefly described. As those skilled in the art will recognize, the described embodiments can be modified in various ways without departing from the spirit or scope of the invention. Therefore, the drawings and description are considered to be exemplary in nature and not restrictive.
[0027] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings.
[0028] Example 1: Preparation process and standard formula for 35W standard type This example describes in detail the complete preparation process and standard formula used for 35W low-power lamp.
[0029] Step 1: Preparation of the discharge liner. Select a high-purity SiO2 quartz glass tube with an outer diameter of 10mm and a wall thickness of 1.2mm, and cut it into 45mm lengths.
[0030] The middle section is heated to 1900℃ using a foaming machine and blown into an olive-shaped bubble with a length of 15mm and a maximum diameter of 12mm. The upper electrode assembly 06 with a spiral electrode head is inserted into one of the pins and its position is adjusted so that its top is 2.5mm from the center of the bubble.
[0031] The high-temperature oxy-fuel flame of the sealing vehicle is used to heat the tube pin to 2100°C to melt it. Then, it is quickly pressed by a pneumatic pressure head to make the quartz glass wrap around the molybdenum electrode rod and seal it tightly.
[0032] Place the pre-sealed semi-finished product into a vacuum molybdenum wire furnace.
[0033] Set the heating curve: heat up to 1050℃ at a rate of 300℃ / h, hold for 7 hours, and maintain the vacuum degree in the furnace at 1×10^-4 Pa.
[0034] This process aims to deeply remove OH groups from the quartz material. It is then slowly cooled to room temperature at a rate of 50°C / h.
[0035] Inside the inert gas glove box, a custom-made filler is added from the open end. The filler formulation is: sodium iodide (NaI), thulium iodide (TmI3), and strontium iodide (SrI2), with a mass ratio of 1:1.5:2.5.
[0036] Insert the lower electrode assembly 07, adjust the electrode distance to 2.5mm, and clamp it securely. Using a Plasma-Flame device, ignite the plasma torch under argon protection, set the power to 3kW, and scan the heating nozzle area until it melts and seals. Subsequently, perform localized sealing reinforcement again at the molybdenum sheet location.
[0037] Step 2: Assemble the irregular molybdenum support, fit a 20mm long ceramic insulating tube 16 on it, and spot weld a degassing plate 13 at a specific position.
[0038] Step 3: Connecting the Inner Tank to the Support. Weld one end of the support to the molybdenum rod 09 of the discharge inner tank. Insert a 10mm long insulating sleeve 15 into the other end of the support, then connect the molybdenum connecting rod, and weld the two ends together through the molybdenum sheet 10.
[0039] Bend the end of the inner tube near the lamp holder at a 90-degree angle, and then insert the insulating sleeve 15 and connect it to another molybdenum connecting rod.
[0040] Step 4: Sealing and venting the outer tube. Place the assembly into the UV filter quartz glass shell 19.
[0041] High-purity nitrogen gas is continuously introduced into the external exhaust pipe as an inert gas for protection (14), with the flow rate controlled at 0.5 L / min. A sealing machine is used to press and form the sealing interface (04) at approximately 2000℃.
[0042] Then, the vehicle was transferred to the exhaust truck, where a vacuum was drawn to 10^-3 Pa, heated to remove gas, and filled with a mixture of xenon and argon (mass ratio 100:0.7). Finally, the exhaust pipe was sealed and cut.
[0043] Step 5: Lamp head assembly. Pass the exposed molybdenum connecting rod through the connecting channel 01-4 of lamp head 01, ensuring that 3mm is exposed.
[0044] Welding was performed using a resistance welding machine. The lamp holder was fixed with powder inside cavity 01-3 and then dried in a 110℃ oven for 30 minutes.
[0045] The key process parameters for preparation are controlled as shown in the table below:
[0046] Example 2: 12W micro lamp manufacturing process and low-power formula optimization. For 12W micro lamps, the process parameters need to be finely adjusted to adapt to the physical limitations brought about by the small size.
[0047] Formula adjustment: Due to the low power and relatively low arc temperature, in order to improve luminescence efficiency, the halide ratio needs to be adjusted to increase the concentration of luminescent metal atoms.
[0048] The mixture of sodium iodide, thulium iodide, and strontium iodide was used in a ratio of 1:1:1.5. The mass ratio of xenon to argon was adjusted to 100:0.5 to reduce heat loss through gas conduction and maintain the arc temperature.
[0049] Process adjustments: During the preparation of the discharge inner liner, the bubble size was reduced, with a bubble diameter of only 8mm. The hydroxyl removal treatment time was shortened to 6 hours to avoid deformation of the thin-walled quartz tube.
[0050] The plasma sealing power was reduced to 2kW, and a fine-tuning method was used for sealing to prevent burn-through of the tube wall. In the support assembly stage, the length of the insulating sleeve 15 was reduced to 8mm, and the inner diameter was reduced to 1.0mm.
[0051] The support bracket 11 is made of 0.3mm thick ultra-thin molybdenum sheet by stamping. When sealing the outer tube, the inert gas protection flow rate is reduced to 0.2L / min.
[0052] The pressure of the protective gas is slightly lower than that of the standard model to accommodate the pressure requirements of the small-volume inner liner.
[0053] During the welding process, the exposed length of the molybdenum connecting rod is strictly controlled to 3mm. Micro-spot welding technology is used to ensure that the weld points are small and strong, without affecting the confined space inside the lamp holder. A comparative analysis of the process parameters in this embodiment is shown in the table below:
[0054] Example 3: Optimization of Manufacturing Process and High-Load Formula for 75W High-Power Lamp For 75W high-power lamps, the key process focus is on enhancing the heat resistance and explosion resistance of the structure.
[0055] Formula adjustment: At high power, the arc temperature is extremely high, requiring a stronger halogen cycle to prevent the electrode from evaporating too quickly. Using a sodium iodide:thulium iodide:strontium iodide ratio of 1:2:3.5, increasing the proportion of strontium iodide helps improve arc voltage and thermal stability.
[0056] The mass ratio of xenon to argon was adjusted to 100:1. Increasing the argon content helps to buffer internal pressure fluctuations under high power and stabilize the electric arc.
[0057] Process adjustments: The wall thickness of the quartz glass tube was increased to 1.5 mm. The hydroxyl removal treatment time was extended to 8 hours to ensure that hydroxyl groups in the thick-walled material were fully removed.
[0058] The plasma sealing power was increased to 4kW to ensure full fusion sealing of thick-walled pipe openings. The support bracket 11 was thickened to 0.5mm, and an auxiliary degassing plate was added to enhance the suction capacity while welding the degassing plate 13.
[0059] During the sealing of the outer tube, the inert gas protection flow rate is increased to 1.0 L / min, forming a stronger positive pressure protection to prevent external oxygen backflow. The pressing and molding pressure of the sealing interface 04 is increased by 20%.
[0060] The lamp holder mounting base 01-1 is made of metal. After welding, the cavity 01-3 is filled with inorganic lamp holder fixing powder instead of organic silicone to withstand higher working temperatures. The oven drying temperature is set to 120℃.
[0061] The performance verification data for this embodiment after process optimization is shown in the table below:
[0062] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various variations or substitutions within the technical scope disclosed in the present invention, and these should all be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A manufacturing process for a low-power sunrise lamp, characterized in that, Includes the following steps: (1) Preparation of the discharge inner tube: Select a high-purity SiO2 quartz glass tube and heat it with a bubble machine to form an olive-shaped bubble; insert an electrode assembly with a spiral electrode head, and quickly press and seal the tube pins to the fusion point by heating them with a high-temperature flame in a sealing vehicle; place the sealed quartz bubble into a vacuum molybdenum wire furnace and operate at 1050℃ for 6-8 hours with a high vacuum environment to remove OH groups; after cooling to room temperature, add a customized filler from the other end; insert another electrode assembly with a spiral electrode head, adjust the electrode spacing and fix it; after filling with xenon and argon, use Plasma-Flame technology to seal the glass tube opening tightly, and then seal it again at the molybdenum sheet; cut off the excess glass tube and burn the opening; (2) Pretreatment of the stent: Prepare an irregularly shaped molybdenum stent, fit a ceramic insulating tube (16) on the stent, and weld a degassing plate (13); (3) Assembly of inner liner and bracket: Weld one end of the bracket to the molybdenum rod (09) of the discharge inner liner; after putting on the insulating sleeve (15) at the other end of the bracket, connect the molybdenum connecting rod and weld it through the molybdenum sheet (10); bend the end of the discharge inner liner near the lamp head, put on the insulating sleeve (15) and connect another molybdenum connecting rod; put the assembly into the lamp body; (4) Sealing and venting of the outer tube: Fix the assembly, cover it with a UV-filtering quartz glass shell (19), and introduce inert gas (14) through the outer vent pipe for protection; use a sealing machine to press and form a sealing interface (04); perform vacuum treatment to remove impurities, fill with protective gas, and then seal and cut the vent pipe; (5) Lamp holder assembly: Pass the molybdenum connecting rod through the metal lamp foot tube post (01-2) at the bottom of the lamp holder (01) and expose 3mm, and then weld it; (6) Curing: Fill the lamp holder cavity (01-3) with lamp holder fixing powder and dry and cure at 100-120℃.
2. The preparation process according to claim 1, characterized in that, The vacuum level of the high vacuum environment mentioned in step (1) is 1×10^-4 Pa to 1×10^-5 Pa; The cooling rate of the slow cooling process is controlled at 30-50℃ / h; the power density of the Plasma-Flame is set to 2-4kW, and the scanning speed is 5-10mm / s to ensure that there are no bubbles or cracks in the sealing area.
3. The preparation process according to claim 1, characterized in that, The insulating sleeve (15) described in step (3) is positioned between the bottom of the support bracket (11) and the molybdenum sheet (10), and the length of the insulating sleeve (15) covers more than 80% of the exposed part of the molybdenum connecting rod. The bending angle is 85-95 degrees, and the bending radius is greater than 5mm to prevent the quartz tube from breaking.
4. The preparation process according to claim 1, characterized in that, The inert gas (14) mentioned in step (4) is high-purity nitrogen or argon, with an introduction flow rate of 0.2-1.0 L / min, and positive pressure protection is maintained throughout the sealing process; the vacuum degree of the vacuum treatment reaches the level of 10^-3 Pa, and the heating and degassing temperature is 350-450℃.
5. The preparation process according to claim 1, characterized in that, The welding described in step (5) is performed by resistance welding or micro-beam plasma welding. The welding current is 50-150A and the welding time is 0.1-0.5 seconds to ensure that a metallurgical bond is formed between the molybdenum connecting rod and the metal lamp base column (01-2) and the contact resistance is less than 5mΩ.
6. The preparation process according to claim 1, characterized in that, The custom filler comprises a metal halide consisting of sodium iodide, thulium iodide, and strontium iodide in a mass percentage ratio of 1:1-2:1-3.
5. This ratio is used to form a halogen cycle under the action of an electric arc, adjusting the color temperature to the range of 3000-6000K.
7. The preparation process according to claim 1, characterized in that, The mass percentage of xenon gas to argon gas introduced in step (1) is 100:0.5-1; This gas ratio is used to reduce the starting voltage to around 10,000V and enhance the stability and penetration of the electric arc.
8. The preparation process according to claim 1, characterized in that, The lamp holder fixing powder mentioned in step (6) is a silicate composite powder; The drying and curing time is 20-40 minutes. The adhesive layer formed after curing has both insulation and shock absorption properties.
9. The preparation process according to claim 1, characterized in that, The sealing position (18) of the discharge inner liner (03) is sealed using a high-temperature oxy-fuel flame, with the flame temperature controlled at 2000-2200℃ and the pressing pressure at 0.5-1.5 MPa, to ensure that the molybdenum sheet (10) and the quartz glass tube (17) form an airtight seal without stress concentration.
10. The preparation process according to claim 1, characterized in that, The process described is suitable for manufacturing low-power solar lamps with a power of 12-75W. The prepared Xuguang lamp has a lamp efficacy greater than or equal to 100 lm / W, a color rendering index Ra greater than or equal to 90, and a starting voltage of 9800-10500V.